2001
DOI: 10.1108/00242530110390451
|View full text |Cite
|
Sign up to set email alerts
|

User perceptions of library effectiveness in Malaysian agricultural libraries

Abstract: This study investigated those factors that contribute positively in shaping users’ perceptions of library effectiveness. A questionnaire‐based survey of five major agricultural libraries in Malaysia was conducted. It was found that the adequacy of collections, services and facilities were closely linked to the perceptions of library effectiveness. Certain other factors contributing positively to the perception of library effectiveness were the adequacy and effectiveness of library promotion, involvement of use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Majid et al (2001) maintained that lack of current, accurate, sufficient, relevant and timeliness of information could hinder agricultural research and development. Aina (2007) suggested that the road to success for information centres in Africa is the provision of relevant and timely information to rural communities.…”
Section: Quality Of Informationmentioning
confidence: 98%
See 1 more Smart Citation
“…Majid et al (2001) maintained that lack of current, accurate, sufficient, relevant and timeliness of information could hinder agricultural research and development. Aina (2007) suggested that the road to success for information centres in Africa is the provision of relevant and timely information to rural communities.…”
Section: Quality Of Informationmentioning
confidence: 98%
“…It is widely known that low awareness is among the primary reason for under-utilization of information services (Majid et al, 2001). Similarly, Shibanda (1999) maintained that awareness of information services is usually associated with the awareness stage, where farmers learn about new ideas by being introduced to new sources of information such as farmers training centres, extension agents, agricultural research institutions, film shows, farm radio, newspapers/magazines, government officials and cooperatives societies.…”
Section: Awareness Of Servicesmentioning
confidence: 99%
“…Hernon et al (1999) conducted a series of factor analyses on over 100 variables and found that the dimensions of library service quality included: guidance, waiting time, electronic services, staff (including obtainment courtesy, accessibility of services, and friendliness), and accurate places of data, normal operations of equipments, handling time of data delivery, library buildings and environment, library facilities (such as drinking fountains), data that met users' needs, and so forth. Majid et al (2001) applied a questionnaire survey to investigate all possible factors that had great impacts on library performances. The results showed that collections, equipments, and physical facilities were viewed as most important issues.…”
Section: Library Service Qualitymentioning
confidence: 99%
“…Although the manufacturing and Services sectors have played a remarkable role in transforming Malaysia towards an industrial society, the contribution of the agricultural sector is still very significant (Majid et al 1998). Commodities such äs palm oil, natural rubber, and tropical timber earn precious foreign exchange for the country Several research organisations in Malaysia are engaged in high quality research to improve agricultural productivity Libraries in the field of agriculture and allied disciplines, äs compared to other S&T disciplines in Malaysia, have the most comprehensive and well-developed collections, Services and facilities (Szarina 1992).…”
Section: The Malaysian Scenariomentioning
confidence: 99%